Unmasking Singapore's 2020 General Elections : COVID-19 and the Evolving Political Landscape - Singh, Bilveer, 1956-; Walid Jumblatt Abdullah; Tan, Felix (Singapore : World Scientific Publishing Co Pte Ltd, 2021)
On 10 July 2020, Singapore held its 18th general elections in history and the 13th since independence in 1965.
Includes bibliographical references and index.
Keywords: Elections -- Singapore; Singapore -- Politics and government -- 21st century; COVID-19 (Disease) -- Political aspects -- Singapore